2022
DOI: 10.3390/ph15030305
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Immune Response in Hospitalized Patients with Moderate and Severe COVID-19

Abstract: A low 25-hydroxyvitamin D (25(OH)D) level is considered as an independent risk factor for COVID-19 severity. However, the association between vitamin D status and outcomes in COVID-19 is controversial. In the present study we investigate the association between the serum 25(OH)D level, immune response, and clinical disease course in patients with COVID-19. A total of 311 patients hospitalized with COVID-19 were enrolled. For patients with a vitamin D deficiency/insufficiency, the prevalence of severe COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…A study conducted in the United States showed that patients with a positive SARS-CoV-2 test and a 25(OH)D concentration of 15 ng/mL compared to 40 ng/mL had a 20% greater risk of hospitalization (p = 0.009) and an increased risk of mortality by 53% (p = 0.001) [19]. The same results were obtained in a study of 311 hospitalized COVID-19 patients: low serum 25(OH)D concentrations were found in patients with poorer clinical outcomes compared to those with a moderate and mild clinical course (p = 0.001) [10].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…A study conducted in the United States showed that patients with a positive SARS-CoV-2 test and a 25(OH)D concentration of 15 ng/mL compared to 40 ng/mL had a 20% greater risk of hospitalization (p = 0.009) and an increased risk of mortality by 53% (p = 0.001) [19]. The same results were obtained in a study of 311 hospitalized COVID-19 patients: low serum 25(OH)D concentrations were found in patients with poorer clinical outcomes compared to those with a moderate and mild clinical course (p = 0.001) [10].…”
Section: Discussionsupporting
confidence: 67%
“…Recently published systematic reviews and meta-analyses have demonstrated that vitamin D insufficiency and deficiency are highly prevalent in patients with moderate and severe COVID-19 [1,17]. At present, there are sufficient data to demonstrate that a low serum 25(OH)D concentration increases the disease severity and risk of death in patients with COVID-19 [10,18]. A study conducted in the United States showed that patients with a positive SARS-CoV-2 test and a 25(OH)D concentration of 15 ng/mL compared to 40 ng/mL had a 20% greater risk of hospitalization (p = 0.009) and an increased risk of mortality by 53% (p = 0.001) [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also found that a decreased CD4/CD8 ratio is associated with low 25(OH)D levels [ 81 ] and that the administration of 5000–10,000 IU of vitamin D3 is attributable to an increase in the CD4/CD8 ratio, reflecting immune regulation [ 76 , 82 ]. Serum 25(OH)D level ≤ 11.4 ng/mL is associated with the stimulation of Th2 and the downregulation of Th17 cell polarization of adaptive immunity in patients with COVID-19 [ 83 ]. In this sense, the trial conducted by Torres and colleagues showed that the administration of a high dose of vitamin D equal to 10,000 IU/day leads to an increase in anti-inflammatory cytokines, such as IL10, and higher levels of CD4+ T cells, which may contribute to decreasing the inflammatory state in severe forms of COVID-19.…”
Section: Resultsmentioning
confidence: 99%